2017
DOI: 10.1038/s41598-017-09205-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the N-terminal transmembrane domain of StarD7 and its importance for mitochondrial outer membrane localization and phosphatidylcholine transfer

Abstract: StarD7 facilitates phosphatidylcholine (PC) transfer to mitochondria, and is essential for mitochondrial homeostasis. However, the molecular mechanism for PC transfer by protein remains poorly understood. Herein, we describe a putative novel transmembrane (TM) domain C-terminal to the mitochondria-targeting signal (MTS) sequence at the N-terminus of StarD7. The mature form of StarD7 is integrated and/or associated onto the outer leaflet of the outer mitochondrial membrane (OMM) in HEPA-1 and HepG2 cells. A tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 38 publications
0
28
2
Order By: Relevance
“…To define how PARL affects sorting of STARD7, we first determined the localization of STARD7 within mitochondria and fractionated mitochondria purified from PARL +/+ cells by osmotic swelling (Fig A). In contrast to previous reports (Horibata et al , ), STARD7 was protected against externally added protease in intact mitochondria but was degraded upon disruption of the OM (Fig A). It thus shows a similar behavior than the i ‐AAA protease YME1L, which is active in the IMS, whereas matrix‐localized proteins such as mtHSP70 became accessible to externally added protease only upon solubilization of the IM (Fig A).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…To define how PARL affects sorting of STARD7, we first determined the localization of STARD7 within mitochondria and fractionated mitochondria purified from PARL +/+ cells by osmotic swelling (Fig A). In contrast to previous reports (Horibata et al , ), STARD7 was protected against externally added protease in intact mitochondria but was degraded upon disruption of the OM (Fig A). It thus shows a similar behavior than the i ‐AAA protease YME1L, which is active in the IMS, whereas matrix‐localized proteins such as mtHSP70 became accessible to externally added protease only upon solubilization of the IM (Fig A).…”
Section: Resultscontrasting
confidence: 99%
“…In contrast to this study, STARD7 has recently been reported to be localized to the mitochondrial OM (Horibata et al , ). To assess whether accumulation of STARD7 at the mitochondrial surface is sufficient to preserve mitochondrial activities, we replaced the mitochondrial targeting sequence and transmembrane region of STARD7 by the membrane anchor of the OM proteins TOMM70 or AKAP1 (Fig EV6A) and expressed these STARD7 variants in STARD7 −/− cells.…”
Section: Resultscontrasting
confidence: 98%
See 2 more Smart Citations
“…Loss of StarD7 causes a significant reduction in mitochondrial PC levels, impaired respiratory activity, overproduction of reactive oxygen species, and disrupted cristae structures (31,32). StarD7 resides in the outer mitochondrial membrane (OMM) and is believed to shuttle PC between ER and OMM at ER-mitochondria contact sites (40,64). As ceramide biosynthesis occurs in mitochondria-associated ER membranes (MAMs; (61,62)) and is upregulated in response to various stress stimuli (8,9), it is conceivable that the local concentration of ceramides at ER-mitochondria contact sites can rise to a level where it affects StarD7-mediated mitochondrial PC import.…”
Section: Downloaded Frommentioning
confidence: 99%